2009
DOI: 10.2214/ajr.08.1299
|View full text |Cite
|
Sign up to set email alerts
|

MDCT Pulmonary Angiography Evaluation of Pulmonary Embolism in Children

Abstract: The prevalence of PE may be more common among pediatric patients than previously reported and has a similar distribution to that in adult patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 38 publications
4
38
1
1
Order By: Relevance
“…1). Kritsaneepaiboon et al [4] found a lower lobe predilection (right lower lung lobe>left lower lung lobe) of pulmonary embolism in children, as seen in adults. Thus, detailed assessment of pulmonary arteries in both lower lung lobes should be emphasized in routine clinical practice.…”
Section: Ct Findings Of Acute Pulmonary Embolismmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Kritsaneepaiboon et al [4] found a lower lobe predilection (right lower lung lobe>left lower lung lobe) of pulmonary embolism in children, as seen in adults. Thus, detailed assessment of pulmonary arteries in both lower lung lobes should be emphasized in routine clinical practice.…”
Section: Ct Findings Of Acute Pulmonary Embolismmentioning
confidence: 99%
“…Studies have shown a high diagnostic performance of multidetector CT pulmonary angiography for pulmonary embolism detection in children [3, 4]. Compared with central pulmonary emboli, identification of peripheral (subsegmental) pulmonary embolism in children is more difficult due to the small size of pulmonary vessels of children.…”
Section: Ct Findings Of Acute Pulmonary Embolismmentioning
confidence: 99%
See 3 more Smart Citations